1999
DOI: 10.1159/000012339
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Adjustment to Inflammatory Bowel Disease: A Model of Psychosocial Intervention in Non-Psychiatric Patients

Abstract: Background: There is no consensus about the most appropriate psychosocial interventions for people with inflammatory bowel disease (IBD) or the most appropriate criteria by which to select which patients might benefit from the available interventions. Nonetheless the perception that stress and other subjective factors contribute to suffering in IBD is persistent and professionals are often called upon to offer appropriate support. A model of normal psychosocial adjustment to IBD and the interventions which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…The present results are in keeping with several published reports on the effects of nonpharmacological intervention programs in patients with IBD, most of which consisted of one or several components of mind-body therapy, mostly stress reduction and relaxation training [9, 25, 26, 57]. Similar to our own results, the vast majority of previous studies found improvements primarily in psychological rather than clinical parameters, although one study reported improvements in the use of anti-inflammatory drugs following relaxation training [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present results are in keeping with several published reports on the effects of nonpharmacological intervention programs in patients with IBD, most of which consisted of one or several components of mind-body therapy, mostly stress reduction and relaxation training [9, 25, 26, 57]. Similar to our own results, the vast majority of previous studies found improvements primarily in psychological rather than clinical parameters, although one study reported improvements in the use of anti-inflammatory drugs following relaxation training [26].…”
Section: Discussionsupporting
confidence: 91%
“…This may have contributed to a selection bias, which favored individuals who were a priori interested and open to alternative treatment approaches, who attribute changes in disease activity to psychological stress, and may accordingly have had positive expectations regarding the efficacy of mind-body therapy. It is not known whether patients’ acceptance and openness towards alternative treatment options may increase the success of such therapies [57]. Clearly, further studies are needed to investigate the potential of mind-body therapy to serve as an adjunct to standard medical therapy in IBD patients with higher disease activity, different degrees of psychological comorbidities and varying degrees of acceptance of mind-body medicine.…”
Section: Discussionmentioning
confidence: 99%
“…This sequential model that was developed for preventing relapse in depression [16]may potentially apply to any type of psychiatric disorder [13]or when psychotherapy is associated with medical illness [21, 22]. Marks [23]suggested that current prevailing therapeutic mechanisms for explaining therapeutic effectiveness in psychotherapy are about to change.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, there are often opportunities to intervene to reduce uncertainty, to augment tolerance of irreducible uncertainty, and to promote meaningful responses to irreducible suffering in chronic disease in medical patients [12]. Recognizing that psychosomatic expertise is required to respond effectively to these complex sources of suffering, symptoms, and impairment, even in the absence of psychiatric disease, is an argument for the integration of psychosomatic experts within multidisciplinary medical/surgical teams (not merely as consultants for identified "cases") and an argument against exclusively diagnosis-based models of treatment and professional remuneration.…”
mentioning
confidence: 99%